2016
DOI: 10.1128/jvi.02439-15
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recognition of Influenza A Viruses by M158–66Epitope-Specific CD8+T Cells Is Determined by Extraepitopic Amino Acid Residues

Abstract: Natural influenza A virus infections elicit both virus-specific antibody and CD4؉ and CD8 ؉ T cell responses. Influenza A virusspecific CD8؉ cytotoxic T lymphocytes (CTLs) contribute to clearance of influenza virus infections. Viral CTL epitopes can display variation, allowing influenza A viruses to evade recognition by epitope-specific CTLs. Due to functional constraints, some epitopes, like the immunodominant HLA-A*0201-restricted matrix protein 1 (M1 58 -66 ) epitope, are highly conserved between influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 78 publications
4
49
0
Order By: Relevance
“…The use of this in vitro coculture system and isogenic influenza viruses with different M1 protein-encoding gene segments allowed us to detect differences in influenza virus replication in the presence of M1 58-66 -specific CD8 ϩ T lymphocytes. M1 58-66 -specific CD8 ϩ T lymphocytes reduced replication of a virus with extra-epitopic amino acid residues of the human signature to a lesser extent than that with an M1 protein with an avian signature, in concordance with the impaired kinetics and extent of M1 58-66specific CD8 ϩ T lymphocyte activation shown previously (27).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The use of this in vitro coculture system and isogenic influenza viruses with different M1 protein-encoding gene segments allowed us to detect differences in influenza virus replication in the presence of M1 58-66 -specific CD8 ϩ T lymphocytes. M1 58-66 -specific CD8 ϩ T lymphocytes reduced replication of a virus with extra-epitopic amino acid residues of the human signature to a lesser extent than that with an M1 protein with an avian signature, in concordance with the impaired kinetics and extent of M1 58-66specific CD8 ϩ T lymphocyte activation shown previously (27).…”
supporting
confidence: 83%
“…First, in the ViroSpot microneutralization assay, virus replication is monitored in Madin-Darby canine kidney (MDCK) cells (28), which do not express any HLA molecules. Therefore, adherent A549, A549-HLA-A*0201 ϩ (A549A2), and A549-HLA-B*2705 ϩ (A549B27) cells were used to study virus replication in the presence of human CD8 ϩ T lymphocytes, as A549 cells are highly susceptible to infection with influenza viruses (27) and the HLA-transgenic cells are capable of presenting the HLA-A*0201-restricted M1 58-66 and HLA-B*2705-restricted NP 174-184 epitopes, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protection against homologous and heterologous virus appears to be long lasting as IAV-nanovax vaccination also conferred protection in mice challenged at 100 days post vaccination (Figure 6). While the IAV-nanovax formulation tested herein contained only IAV HA and NP proteins, studies have demonstrated that immunity directed against additional IAV proteins such as NA and M1 can enhance protection (47,48). One of the benefits of our nanovaccine platform is the ability to easily "plug and play" new antigens within the formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent development of universal influenza vaccines is focused on the use of conserved peptides or proteins as antigens with different adjuvants and administration methods to induce immune response (26)(27)(28)(29). Expression of the conserved regions of IAV proteins by using viral vector systems can induce CD8 + T cells against lethal IAV challenge in animals, but it still only recognizes one target (30).…”
Section: Discussionmentioning
confidence: 99%